The detrimental clinical impact of severe angiographic vasospasm may be diminished by maximal medical therapy and intensive endovascular treatment. (10th October 2014) - Mortimer, Alex Mark; Steinfort, Brendan; Faulder, Ken; Bradford, Celia; Finfer, Simon; Assaad, Nazih; Harrington, Timothy
Abstract : Objective: Severe angiographic vasospasm (aVSP) is a risk factor for poor functional outcome following subarachnoid hemorrhage. We investigated the impact of angiographic surveillance and intensive endovascular treatment using transluminal balloon angioplasty (TBA) and/or verapamil infusion for severe aVSP through comparison of clinical outcomes in patients of similar presenting grade but with no/mild vasospasm. Methods: This was an analysis of prospectively acquired clinical trial data. World Federation of Neurosurgical Societies (WFNS) grade 1–2 patients presenting within 72 h were included. Angiographic screening for vasospasm was undertaken at days 5–7 or in response to clinical deterioration. Severe aVSP was defined as >50% luminal narrowing on digital subtraction angiography. Treatment was instituted on the basis of radiographic findings and/or clinical deterioration. Discharge destination and favorable clinical outcomes (discharge Glasgow Outcome Score (GOS) 4–5, 90 day modified Rankin Scale (mRS) score 0–2, and GOS 4–5) for patients with severe aVSP were compared with those without significant vasospasm. Statistical analysis was undertaken using Fisher's exact test. Results: 63 WFNS grade 1–2 patients with minimal vasospasm were compared with 17 WFNS grade 1–2 patients with severe aVSP treated with induced hypertension and endovascular therapy. Results were available in 62 and 16 patients, respectively. Rates of favorable outcome did not differ significantly between the two groups. For patients with treated severe vasospasm, 90 day mRS 0–2 was seen in 15/17 (88.2%) and GOS 4–5 was achieved in 16/17 (94.1%). Conclusions: An intensive endovascular approach of TBA and/or intra-arterial verapamil in combination with induced hypertension for severe aVSP may result in comparable clinical outcomes to those without vasospasm.